Do Parents Benefit it from School Health Risk Reduction? - Mahasuweerachai, Phumsith (Asian Journal of Applied Economics, 2013)
The choice experiment method was applied to determine parent’s preferences and monetaryvalues of risk reductions on three related health issues in school, lead contamination inschool drinking water, diarrhea from food contamination, and accident from outdoor playground.Data were obtained from face-to-face interview of 672 respondents in three regions ofThailand. Lead contamination is the greatest concern among parents as reflected by thelargest coefficients of risk reduction levels and the highest amount of monetary values elicitedfrom parent’s preferences. The other two issues are considered of equal importance. However,parents seem insensitive to the changes of risk reductions of these two issues revealingthe scope insensitivity. Given the scope insensitivity, choice experiment may be seen as apromising method to determine preferences and monetary values of health related issuesthat have no appropriate or precise financial proxy available. Keywords: Non-market valuation, safety in school, health risk reduction JEL Classification: D61, I10, I31